2016
DOI: 10.1158/0008-5472.can-16-0651
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Exosomes Promote Melanoma Aggressiveness through Fatty Acid Oxidation: A Novel Mechanism Linking Obesity and Cancer

Abstract: Malignant progression results from a dynamic cross-talk between stromal and cancer cells. Recent evidence suggests that this cross-talk is mediated to a significant extent by exosomes, nanovesicles secreted by most cell types and which allow the transfer of proteins, lipids, and nucleic acids between cells. Adipocytes are a major component of several tumor microenvironments, including that of invasive melanoma, where cells have migrated to the adipocyte-rich hypodermic layer of the skin. We show that adipocyte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
270
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(300 citation statements)
references
References 25 publications
8
270
0
4
Order By: Relevance
“…Loss of PTEN is often observed in brain metastases and cell lines derived from brain metastases (113). Also exosomes derived from adipocytes have been shown to confer migration-promoting properties to melanoma cells through transfer of proteins involved in fatty acid oxidation (114). These observations might explain why obese melanoma patients have a poorer prognosis in comparison to non-obese melanoma patients (114).…”
Section: Exosome Mediated Interplay Between Tumor Cells With Fibroblamentioning
confidence: 99%
“…Loss of PTEN is often observed in brain metastases and cell lines derived from brain metastases (113). Also exosomes derived from adipocytes have been shown to confer migration-promoting properties to melanoma cells through transfer of proteins involved in fatty acid oxidation (114). These observations might explain why obese melanoma patients have a poorer prognosis in comparison to non-obese melanoma patients (114).…”
Section: Exosome Mediated Interplay Between Tumor Cells With Fibroblamentioning
confidence: 99%
“…Lazar and colleagues demonstrated that treating melanoma cells with 3T3-F442A-derived exosomes can enhance cancer cells' ability to migrate and metastasize to the lungs, and such effects were amplified when exosomes were derived from adipocytes of obese mice as opposed to those from lean mice [38]. Adiposederived exosomes were enriched with enzymes of the fatty acid oxidation (FAO) pathway, and providing melanoma cells with these proteins seemed to promote an aggressive phenotype, as pharmacologic inhibition of the FAO pathway in cancer cells abrogated the effects of exosome treatment [38]. While it remains unknown whether exosomes play a role in promoting other types of malignancies associated with obesity, adipose-derived EVs may serve as a mechanism by which excess adiposity promotes cancer initiation or progression.…”
Section: Adipose-derived Evs and Cancermentioning
confidence: 99%
“…Notably, several known associations exist that could link obesity with worsened melanoma outcomes, including germline genetic variants in obesity-related genes associated with melanoma risk, 14 inflammation, 14 obesity-related cytokines, 15 and adipocyte cross-talk. 16 Of particular interest, the IGF-1/PI3K/AKT pathway has been shown to play a key role in the pathogenesis of obesity in cancer, 17 and has also been implicated in resistance to both targeted and immune therapies in melanoma. 18,19 …”
Section: Introductionmentioning
confidence: 99%